Obstacles to the development of the tourism sector in Algeria -Jijel state a model - abdeslam, salima; boussakra, amar (Journal of Social Sciences and Humanities, 2021)
Strategic planning is one of the most important internationally adopted ways to promote sectors that are vital to both economic and social development, especially if there is an effective plan and sufficient capacity to ensure success and the achievement of goals, because success in any area cannot in any way be a product of chance; Real success is the expected result of a combination of factors or so-called success qualifications. We can bring this down even to the various types of life, both social and economic, that are embodied on the ground as models of individual behaviour if it comes to the social aspect and as income and benefits if it relates to the economic aspect. What can be the reason why economic plans of a developmental nature are not successful if there are all possibilities for success, namely, material and human possibilities and effective, integrated plans. This is what has already happened on the ground, specifically in the area of tourism planning in Algeria, where it relates to the most important area of tourism expansion in Algeria, the city of Jejel; Because of its potential for success in the tourism sector (natural, human, material, strategic), which we wanted to present after the study and the field investigation of the reality of the tourism sector in Jigel State and the obstacles to its development. This study contains a number of information and data that illustrate the real causes of the lack of success and decline of the tourism industry in the State of Jegel, despite the Algerian State's desire for the success of this vital sector. To complete this study, the analytical descriptive approach and its main research tools of observation, corresponding to documents, maps and charts have been drawn upon, depending on the requirements and nature of the study.